MENGENAL MODEL PAUD BEYOND CENTRE AND CIRCLE TIME (BCCT) UNTUK PEMBELAJARAN ANAK USIA DINI - Aida Nur Fitri; Christine Steffani; Salsabila Afifah (Jurnal Anak Usia Dini Holistik Integratif (AUDHI), 2022)
AbstractThis article discusses the BCCT learning model or known as the Sentra model that describes the history, shortcomings and advantages, main characteristics, principles, and objectives of this BCCT / Sentra model. This article was created considering the importance of learning models in the implementation of early childhood education, so that it is expected to expand knowledge, especially educators as parties who have an important role in the implementation of education for early childhood. This research uses this type of qualitative research by referring to descriptive analysis from a variety of relevant sources. The type of study used is literature study by collecting information from books, journals, article discussions and others. The results of this study found that the learning model that is suitable for use in early childhood education in Indonesia is the BCCT / Sentra learning model, because it does not require much equipment, but children's intelligence can still be optimized.AbstrakArtikel ini membahas mengenai model pembel ajaran BCCT atau dikenal dengan model Sentra yang memaparkan sejarah, kekurangan dan kelebihan, ciri utama, prinsip-prinsip, serta tujuan dari model BCCT/ Sentra ini. Artikel ini dibuat mengingat pentingnya model pembelajaran dalam pelaksanaan pendidikan anak usia dini, sehingga diharapkan dapat memperluas pengetahuan khususnya para pendidik sebagai pihak yang memiliki peran penting dalam penyelenggaraan pendidikan bagi anak usia dini. Penelitian ini menggunakan jenis penelitian kualitatif dengan merujuk pada penganalisisan deskriptif dari berbagai sumber yang relevan. Jenis studi yang digunakan yaitu studi kepustakaan dengan mengumpulkan informasi dari buku, jurnal, pembahasan artikel dan lainnya. Hasil dari penelitian ini didapatkan bahwa model pembelajaran yang cocok digunakan dalam pendidikan anak usia dini di Indonesia adalah Model pembelajaran BCCT/ Sentra, karena  tidak memerlukan peralatan banyak, namun kecerdasan anak tetap bisa dioptimalkan.